Comparing Intraperitoneal and Intravenous Personalized ErbB2CAR-T for the Treatment of Epithelial Ovarian Cancer - Naamit Deshet-Unger; Galit Horn; Moran Rawet-Slobodkin; Tova Waks; Ido Laskov; Nadav Michaan; Yael Raz; Vered Bar; Adi Zundelevich; Sara Aharon; Lubov Turovsky; Giuseppe Mallel; et al. (Biomedicines, 2022)
High-grade serous ovarian carcinoma (HGSOC) is the most common type of epithelial ovarian cancer. The majority of cases are diagnosed at advanced stages, when intraperitoneal (IP) spread has already occurred. Despite significant surgical and chemotherapeutic advances in HGSOC treatment over the past decades, survival rates with HGSOC have only modestly improved. Chimeric antigen receptor (CAR)-T cells enable T cells to directly bind to tumor-associated antigens in a major histocompatibility complex-independent manner, thereby inducing tumor rejection. While CAR-T cell therapy shows great promise in hematological malignancies, its use in solid tumors is limited. Therefore, innovative approaches are needed to increase the specificity of CAR-modified T cells against solid tumors. The aim of this study was to assess the efficacy and safety of intraperitoneal (IP) versus intravenous (IV) CAR-T cell therapy in the treatment of HGSOC. We constructed a CAR that targets the ErbB2/HER2 protein (ErbB2CAR), which is overexpressed in HGSOC, and evaluated the functionality of ErbB2CAR on ovarian cancer cell lines (OVCAR8, SKOV3, and NAR). Our findings show that an IP injection of ErbB2CAR-T cells to tumor-bearing mice led to disease remission and increased survival compared to the IV route. Moreover, we found that IP-injected ErbB2CART cells circulate to a lesser extent, making them safer for non-tumor tissues than IV-injected cells. Further supporting our findings, we show that the effect of ErbB2CAR-T cells on primary HGSOC tumors is correlated with ErbB2 expression. Together, these data demonstrate the advantages of an IP administration of CAR-T cells over IV administration, offering not only a safer strategy but also the potential for counteracting the effect of ErbB2CAR in HGSOC. Significance: IP-injected ErbB2CAR-T cells led to disease remission and increased survival compared to the IV route. These findings demonstrate the advantages of IP administration, offering a safe treatment strategy with the potential for counteracting the effect of ErbB2CAR in HGSOC.